2013
DOI: 10.3892/mco.2013.208
|View full text |Cite
|
Sign up to set email alerts
|

Opposite variation tendencies of serum CA724 levels in patients with colon and rectal carcinoma

Abstract: Abstract. The aim of this study was to investigate tumor biomarker carbohydrate antigen 724 (CA724) in the serum of patients with carcinomas of the colon and rectum at various clinical stages. Serum was collected from 51 patients with colon carcinoma (CC) and 49 patients with rectal carcinoma (RC). CA724 levels were then measured in the different groups according to site, TNM classification, gender, age and metastastic status of the patients. The statistical significance of the differences between the groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Zhu et al . showed that there were statistically significant differences in CA724 levels between patients with and without distant metastases19. A meta-analysis demonstrated that CA724 was the most sensitive serum tumor biomarker for the detection of gastric cancer in the Chinese population18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al . showed that there were statistically significant differences in CA724 levels between patients with and without distant metastases19. A meta-analysis demonstrated that CA724 was the most sensitive serum tumor biomarker for the detection of gastric cancer in the Chinese population18.…”
Section: Discussionmentioning
confidence: 99%
“…CA724 is a glycoprotein, with higher levels in gastric 17 18 , colorectal 19 , and breast 20 cancer. Zhu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduction in Tim-3 expression was associated with a loss of Tim-3-expressing cells, because patients undergoing surgery demonstrated no significant attenuation in the mean fluorescence intensity of Tim-3, compared with untreated patients (data not shown). In CRC patients, serum CEA, CA199 and CA724 may be useful in the diagnosis of colorectal carcinoma (31,32). The relationship between the proportion of CD3 -CD56 + NK cells in CRC patients and these serum biomarkers was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate antigen 724 (CA724) was the most correlative serum tumor biomarker for gastric cancer (Chen et al, 2012). It had been recently reported that serum CA724 was closely correlated to tumor staging of CRC patients (Zhu et al, 2014). But, the relationship between serum CA724 levels and prognosis of CRC remained unclear, especially in the patients with normal CEA levels.…”
Section: Introductionmentioning
confidence: 99%